Analisis Karakteristik Material Lokal Kinang Jingkion dari Quarry Apalapsili, Habie Dan Hulikma, Serta Komposisi Campuran Terbaik Untuk Digunakan sebagai Bahan Lapis Pondasi Agregat Kelas A - Lyresica Nurmalasari Sirait; Petrus Bahtiar; Mudjiati Mudjiati (Syntax Literate, 2023)
The main road pavement works carried out in Yalimo Regency are flexible pavements using asphalt as the main adhesive. Asphalt produced outside Papua Island is transported to Jayapura using sea transportation, then transported to Wamena using air transportation, then transported to Yalimo Regency using land transportation, of course the price is not cheap when it arrives in Yalimo Regency. In addition to the price factor of asphalt material due to the relatively high transportation services, another thing that becomes a consideration for the need to use Kinang Jingkion material is the ease factor in working on roads using Kinang Jingkion which allows the local community to work on it using standard equipment that does not really require treatment or specific technology. According to these problems, further research on Kinang Jingkion material is urgently needed. Analysis of the Characteristics of the Local Material of Kinang Jingkion from the Apalapsili, Habie and Hulikma Quarry, and the Best Mix Composition to be Used as a Class A Aggregate Base Layer presents the results of the analysis related to the characteristics of the local Kinang Jingkion material taken from 3 different quarries namely Apalapsili, Habie and Hulikma, as well as results of testing the composition of the mixture to be used as a Class A Aggregate Base Layer.